Penerapan Model Pembelajaran Inkuiri Dan Media Alat Peraga (Gunung Berapi) Pada Mata Pelajaran IPA SDN 013 Bengkulu Utara - Mellyta Uliyandari; Elly Efrida Lubis (PendIPA Journal of Science Education, 2020)
This study aims to improve the quality of student learning outcomes in science subjects class IV / B SDN 013 Bengkulu Utara, using inquiry methods and teaching aids (volcanoes). The subjects in this study were students in class IV/B of SDN 013 Bengkulu Utara, with 24 students, 14 male students, and 10 female students. The study was conducted in 3 stages, namely: pre-cycle, cycle I and cycle II where each cycle consisted of 4 stages: Planning, Implementing, observing and reflecting. In this study each meeting ends with an evaluation in the form of test questions. The results of the analysis of mastery learning in pre-cycle are still quite low, namely, the results of students' mastery learning are only 33.33% with an average value of 64.79 After making improvements in learning in the first cycle classical learning completeness increased to 50% with an average value of 66.04. Then in the second cycle an increase of 95.85% with an average of 76.25. Based on the results of the study note that the use of inquiry methode and teaching aids (volcanoes) can improve student learning outcomes in science learning in SDN 013 Bengkulu Utara.